HPLC DETERMINATION OF BENZOXAZOLINONE ON JERUJU PLANT (ACANTHUS ILICIFOLIUS): NARRATIVE REVIEW - Nurul Umi Salamah; Imron Wahyu Hidayat; Tiara Mega Kusuma; Heni Setyowati Esti Rahayu; Prasojo Pribadi (Universitas Muhammadiyah Magelang, 2023)
Mangrove plants in Indonesia are the largest in the world, both in terms of area quantity (+42,550 km2) and number of species (+45 species). Mangroves are a diverse group of salt tolerant plants that grow in intertidal tropical and subtropical forests and represent a rich biodiversity of plants, animals and microorganisms. Acanthus ilicifolius is one of the true mangrove plants which is used as medicine. This literature review aims to determine the study of benzoxazolinone compounds in jeruju plants (Acanthus ilicifolius) from previous studies and to determine the methods, plant parts and solvents used. The literature review method related to the jeruju plant (Acanthus ilicifolius) uses an electronic data base google scholar. Nuclear Magnetic Resonance (NMR) spectroscopy analysis method is one of the spectroscopic methods widely used in previous studies, because NMR spectroscopy is useful in determining the structure of a chemical compound, both proton (1H) and carbon (13C) NMR. Jeruju leaf extract contains alkaloids, flavonoids, polyphenols, phenyletanoid glycosides and coumarin compounds. The methanol fraction of jeruju leaf extract has a pharmacological effect to inhibit edema (inflammation). The extraction method used is maceration, because this method is simple method and most widely used. Meanwhile, the solvents that are more widely used are methanol and ethanol solvents.